1997
DOI: 10.1523/jneurosci.17-03-00875.1997
|View full text |Cite
|
Sign up to set email alerts
|

TheDrosophila ergK+Channel Polypeptide Is Encoded by the Seizure Locus

Abstract: The eag family of K+ channels contains three known subtypes: eag, elk, and erg. Genes representing the first two subtypes have been identified in flies and mammals, whereas the third subtype has been defined only by the human HERG gene, which encodes an inwardly rectifying channel that is mutated in some cardiac arrhythmias. To establish the predicted existence of a Drosophila gene in the erg subfamily and to learn more about the structure and biological function of channels within this subfamily, we undertook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 33 publications
3
98
0
Order By: Relevance
“…Structural analysis of Eag1 has revealed that the eag domain, which is required for slow deactivation in hsErg1 and mmErg1 (27,29), docks on the CNBHD (26). An eag domain has not been identified in DmErg and CeErg (19), suggesting that loss of eag domain function might explain fast deactivation in the DmErg-like gating phenotype. We found no evidence for an eag domain in nematode Ergs or NvErg2-5 in the verified or predicted coding sequence or genome sequence.…”
Section: Our First Expression Of Ceerg Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural analysis of Eag1 has revealed that the eag domain, which is required for slow deactivation in hsErg1 and mmErg1 (27,29), docks on the CNBHD (26). An eag domain has not been identified in DmErg and CeErg (19), suggesting that loss of eag domain function might explain fast deactivation in the DmErg-like gating phenotype. We found no evidence for an eag domain in nematode Ergs or NvErg2-5 in the verified or predicted coding sequence or genome sequence.…”
Section: Our First Expression Of Ceerg Inmentioning
confidence: 99%
“…Temperature-sensitive mutations in the seizure locus that encodes DmErg cause bursts of uncoordinated motor output (19) suggestive of changes in subthreshold excitability. The Caenorhabditis elegans Erg ortholog (CeErg, encoded by unc-103) has not been functionally expressed, but genetic analysis demonstrates that it regulates the excitation threshold of vulva muscles in females and protractor muscles in males (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…1B). These behavioral and electrophysiological phenotypes of dao are very similar to sei mutants, which disrupt Ergtype K + channels (3,4,(9)(10)(11). However, complementation tests revealed that dao and sei affect different genes.…”
Section: Resultsmentioning
confidence: 69%
“…Screening for behavioral mutations in Drosophila that perturb neural signaling has been an effective means of identifying key proteins and cellular pathways that regulate excitability. Particularly useful for such studies have been temperature-sensitive (ts) paralytic mutants including paralytic (para) and slowpoke (slo), which encode voltage-gated sodium channels and calcium-activated potassium channels, respectively, and seizure (sei), which encodes the Drosophila ortholog of the voltage-gated human ether-a-go-go-related gene (hERG) potassium channel (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…However, we found that comt; sei ts2 double mutants (Jackson et al 1985;Elkins and Ganetzky 1990;Titus et al 1997;Wang et al 1997) were no more severe than comt mutants alone when measuring lifespan, locomotor defects, or loss of DA neurons (Figure 3, C-E).…”
Section: Resultsmentioning
confidence: 90%